Pemetaan Kajian Tasawuf: Suatu Pendekatan Bibliometrik: Mapping the Study of Sufism: A Bibliometric Approach - Zuhriyyah Hidayati; Siti Maimunah; Mokhamad Syaifudin; Khoirun Niam (University of Darussalam Gontor, Indonesia, 2025)
Tasawwuf,Â or Islamic mysticism,Â occupies a prominent place in Islamic studies. Its literature has contributed greatly to the development of Islamic thought, ethics, and education. However, despite the role and impact of the Sufism literature, it is undeniable that the mapping and its relevance to other studies in a comprehensive bibliometric analysis of this work is lacking. To address this gap, it is critical to explore and measure the scientific outcomes, dissemination, and impact of research related to Sufism mapping. In this bibliometric study, a systematic approach is used to analyze a wide range of academic literature. This analysis begins by collecting relevant research articles from the Scopus database, papers from leading academic databases and repositories and then screening with several filters. Furthermore, we used bibliometric techniques, including citation analysis, co-authorship networks, and keyword mapping, to assess trends, patterns, and connections in the Sufism mapping literature. In conclusion, this bibliometric study offers valuable insights into the scientific contribution of Sufism literature which is closely related to other studies, such as spirituality, mental health, politics, and others. By mapping intellectual networks and identifying influential works and authors, this will facilitate future research directions and promote a greater understanding of the historical and contemporary significance of mapping Sufism studies.